A-09 The Relationship Between Subjective Cognitive Complaints, Depression, and Executive Functioning in mTBI Veterans. (28th August 2020) - Scott, T; Spellman, J; Walker, N; Rivera, J; Waltzman, D; Mcnerney, M; Madore, M
Abstract: Objective: Among individuals with mild traumatic brain injury (mTBI), those with depression report greater subjective cognitive complaints than those without depression. In mTBI patients with general cognitive complaints, depression may account for poor performance on objective neuropsychological measures. This study seeks to expand this research by examining depression, subjective executive functioning (EF) complaints, and objective EF performance in Veterans with mTBI. Method: Fifty-seven Veterans with deployment-related mTBI (12% female; age M = 42.0, SD = 13.6; years education M = 15.0, SD = 1.8) with (n = 29) or without (n = 28) a chart diagnosis of depression. Participants were administered the Behavioral Rating Inventory of Executive Functioning (BRIEF) and objective neuropsychological measures of working memory (i.e., Weschler Adult Intelligence Scale-IV Working Memory Index) and aspects of EF (i.e., Trail Making Test B and Delis-Kaplan Executive Functioning System (D-KEFS) subtests). Results: Principal component analysis identified similar domains of EF to the BRIEF, including: task monitoring (Trail Making Test B, D-KEFS Letter Fluency, and D-KEFS Tower Test, eigenvalue = 1.93) and shifting (D-KEFS: Color-Word Interference Conditions 3 and 4, and Category Switching, eigenvalue = 1.24). Individuals with depression had greater subjective EF complaints in each BRIEF domain than non-depressed individuals (p's ≤ .01). However, subjective complaints in these domains were not related to objective performance (r's = −0.17, -0.19, p's > .05). Moreover, depressed and non-depressed individuals performed similarly on all EF measures (p's > .05). Conclusions: mTBI Veterans with depression report more subjective EF complaints than those without depression. The lack of association between subjective complaints and objective EF performance suggests it is important to treat depression in mTBI patients to remedy perceived cognitive deficits.